Characterization of an Inductance-based Detector in Molecular Communication Testbed Based on Superparamagnetic Iron Oxide Nanoparticles - Ahmed, Doaa; Unterweger, Harald; Fischer, Georg; Schober, Robert; Kirchner, Jens (IEEE SENSORS 2019, 2019)
Molecular communication (MC), using chemicals or particles, is a promising approach to bridge the gaps of conventional communication systems, e.g. in nano-scale or in pipelines. Our testbed depends on superparamagnetic iron oxide nanoparticles (SPIONs) as information carriers, which are detected using a susceptometer. In this paper, we study how the position and distribution of particles near the susceptometer, i.e., coil, affect its detected signal. When the particles move axially through the coil, an increment in the signal is detected. In addition, we observed a nonlinear additive behaviour of inductance in the same axial direction, i.e., changes in inductance due to partial volumes are not additive. An exponentially-like signal is detected when the particles move radially through the coil. Moreover, a linear additive behaviour of inductance is observed in this direction. Increasing the magnetic susceptibility has a significant effect on the detected signal. However, the susceptibility of SPIONs is relatively small in order to keep superparamagnetic properties. The coil inductance depends not only on the volume, or permeability of magnetic particles in its core, but also on how they are distributed inside. <br
Keywords: molecular communication; superparamagnetic nanoparticles; simulation; MC testbed; coils; magnetic fields